Perbandingan Hasil Radiografi Efusi Pleura Pada Proyeksi Right Lateral Decubitus (RLD) Dan Left Lateral Decubitus (LLD) Pada Klinis Dengue Haemoragic Fever (DHF) Di RSU. Wisata Universitas Indonesia Timur - Akhmadi Akhmadi; Rini Hatma Rusli; Muhamad Rudiansyah; Amelia Niwele; Yohannes Hursepunny (Jurnal Sains dan Kesehatan, 2022)
Dengue Hemorrhagic Fever (DHF) is an infectious disease that can be fatal in a relatively short time. This disease is classified as "difficult to differentiate" from other dengue fever diseases. If without quick and appropriate treatment, the sufferer could fall into an even more fatal condition. And generally the supporting action taken is an X-ray examination of the chest to assess the presence of fluid in the pleura as a result of the Aedes Aegypti mosquito virus. The purpose of this research is to know the Comparison of Radiographic Results of Pleura Effusion on Right Lateral Decubitus Projection and LLD ( Left Lateral Decubitus ) in DHF ( Dengue Haemoragic Fever ) case. This research was conducted in RSU.Wisata Radiology installation of Universitas Indonesia Timur with quantitative research method with experimental design approach. Data collection is done by finding literature, observation, interview, and documentation. From the results of the research that the image of pleural effusion with RLD projection ( Right Lateral Decubitus ) shows better radiographic picture in assessing the level of pleural effusion with clinical DHF ( Dengue Haemoragic Fever ).